Health View to Decrease Negative Effect of High Heels Wearing: A Systemic Review - Meizi Wang; Ci Jiang; Gusztáv Fekete; Ee-Chon Teo; Yaodong Gu (Applied Bionics and Biomechanics)
Effective recommendations about how to decrease adverse effects of high heels (HH) need to be provided, since wearing HH is inevitable for most women in their daily life, regardless of their negative impacts on the foot morphology. The main purpose of this systematic review was to summarize studies which have provided specific information about how to effectively offset the negative effects of wearing HH, in the case of women, by means of examining heel height, insole, and heel base support (HBS). Some evidence indicate the following: (i) the range of appropriate heel height for HH shoes is 3.76 cm to 4.47 cm; (ii) compared to small HBS, the larger ones effectively increase gait stability, reduce risk of ankle injury, and improve comfort rating during HH walking; and (iii) the use of a total contact insert (TCI) significantly decreases plantar pressure and the impact on the foot, resulting in higher perceived comfort. It must be noted that these results are based on short-term research; therefore, any conclusions with regard to effects in the long term should be taken with a grain of salt. Nevertheless, future studies should be aimed at combining numerical and experimental methods, in order to provide personal recommendations for HH shoes by considering heel height and HBS size, based on the individual characters (weight, height, and age).